1990
DOI: 10.1148/radiology.177.3.2243967
|View full text |Cite
|
Sign up to set email alerts
|

Graves orbitopathy: correlation of CT and clinical findings.

Abstract: The clinical and high-resolution computed tomographic (CT) findings in 71 patients (142 orbits) with Graves orbitopathy and 20 healthy patients (40 orbits) were retrospectively reviewed. The orbits with orbitopathy were subgrouped at clinical examination into those with (n = 18) and those without (n = 124) optic neuropathy. Mean extraocular muscle diameters and the calculated muscle diameter index were significantly increased in all orbits with ophthalmopathy, particularly in those with optic neuropathy. Grave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
144
4
15

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(176 citation statements)
references
References 0 publications
9
144
4
15
Order By: Relevance
“…10,12,13,18,19 Because of its great importance in DON, apical crowding is quantified with a score first described by Nugent et al 15 and reproduced by many other authors, 1,3,7,9,16 which grades the effacement of the perineural fat as 0 (none), 1 (up to 25%), 2 (25%-50%), or 3 (greater than 50%). 15 Using this method, Nugent et al found severe apical orbital crowding (grade 3) in 12 of 18 orbits with DON but in only 16 of 124 orbits without DON. 15 Neigel et al graded as moderate or severe crowding 79.2% of orbits with DON but only 12.9% of orbits without DON.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,12,13,18,19 Because of its great importance in DON, apical crowding is quantified with a score first described by Nugent et al 15 and reproduced by many other authors, 1,3,7,9,16 which grades the effacement of the perineural fat as 0 (none), 1 (up to 25%), 2 (25%-50%), or 3 (greater than 50%). 15 Using this method, Nugent et al found severe apical orbital crowding (grade 3) in 12 of 18 orbits with DON but in only 16 of 124 orbits without DON. 15 Neigel et al graded as moderate or severe crowding 79.2% of orbits with DON but only 12.9% of orbits without DON.…”
Section: Discussionmentioning
confidence: 99%
“…A categoric score of orbital apical crowding, as described by Nugent et al, 15 was also determined at a predetermined coronal section at the midpoint of the intraorbital optic nerve. The score reflects circumferential effacement of perineural fat by the extraocular muscles (0 ϭ none; 1 ϭ mild, 1%-25%; 2 ϭ moderate, 25%-50%; 3 ϭ severe, Ͼ50%).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some patients with inactive thyroid eye disease and mild proptosis, however, have a markedly increased orbital pressure that can be associated with deep orbital vascular congestion, persistently raised intraocular pressures and, in some cases, optic neuropathy. 2,6 This congestive variantFtermed 'hydraulic' disease by the writer, to distinguish it from the congestion of the active inflammatory phaseFappears commoner with certain races (particularly Asians 7,8 ), this probably being due to their thicker orbital walls and relatively less compliant orbital septum.…”
Section: Introductionmentioning
confidence: 99%